Economic performance of artificial reefs deployed along Tamil Nadu coast, South India - Kasim, Hussain Mohamad; Syda Rao, G.; Rajagopalan, M.; Vivekanandan, E.; Mohanraj, G.; Kandasami, D.; Muthiah, P.; Jagdis, I.; Gopakumar, G.; Mohan, S. (Indian Journal of Fisheries, 2013)
The economics of fishery from artificial reef (AR) and non-artificial reef (NAR) sites by gillnet and hooks & line was studied during 2007-08 from 11 fishing villages in 6 coastal districts of Tamil Nadu. The Tamil Nadu State Fisheries Department fabricated and deployed the reefs under the technical guidance of the Central Marine Fisheries Research Institute (CMFRI). Based on species composition in the catch, the annual gross income was estimated by multiplying each species/group catch with the average landing centre price of the respective species/group. After deducting recurring expenditures on fishing operation, maintenance, interest on capital/investment on reef, crew wages, depreciation on craft, gear and reefs, from the gross income, the average net income of gillnet and hooks & line per unit operation from AR site were `1252 and `4650, respectively; and from NAR site was `449 and `1919, respectively. On an average, the AR site offered economic benefit which was higher by `1705.9 per unit compared to NAR site. Hooks & line units performed better than the gillnet units in both the sites. The payback period towards repayment of AR establishment cost was only 0.21 year. In view of better economic viability and short payback period, deployment of artificial reef is recommended in the near shore waters with proper planning.